Liquid Sugar from Egyptian Treacle: II. Chromatographic Fractionation of the Treacle Colourants with Molecular Sieves - MOHAMED, MOSTAFA A. (The Libyan Journal of Agriculture, 2023)
he present study describes the application of gel filtration technique to the fractionation of the treacle colourants. Some properties of the fractions obtained were also studied.Gel filtration using Sephadex’ G - 25 provided some useful information on the molecular size range of the individual colourants. U.V.-spectroscopic examination of the individual colourants strongly suggested the presence of various groups of chromophores which have intensive absorption in the wavelength range 255 290 nm. The results obtained give an evidence that the treacle colourants contain one or more of the following groups: melanoidines, caramels, products of degradation of reducing sugars and complexes of Cu++ ions with these products. The present work, however, provides a narrow but helpful basis for further investigations.